Emerging Antimicrobial Resistance amongst Common Bacterial Pathogens in Mymensingh Medical College Hospital (Bangladesh Journal of Medical Microbiology, 2016)
Antimicrobial resistance has been coming up as one of the challenging business for treating domiciliary and nosocomial infections. The present study compared rate of resistance towards different commonly used antibiotics for common bacterial pathogens isolated during 2001 to 2003. Regarding Escherichia coli, mentionable increase (p